( The Effect of Type of Bamboo Charcoal and Pyrolization temperature on the isothermal adsorption of Hâ ion Characterization, the chloroform adsorption and the electric conductivity) - G Pohan, H; Yeoul Kim, Hi (Balai Besar Industri Agro, 2007)
The study of the effect of three varieties of bamboo and pyrolization temperature of 400 degree C,500 degree C,600 degree C,and 700 degree C on the isothermal adsorption of H,the adsorption of chloroform and the electrical conductivity of charcoal have been carried out.The study was aimed to the determine characteristic of charcoal to be measured of the adsorption of isothermal ion H+ by using acid solution of acetate 0,1 mole the adsorption of chloroform and the electrical conductivity.The research result shown that the temperature of pyrolization excelsior,the adsorption isothermal ion H+ and the chloroform exelsior but the electrics conductivity progressively lower for all bamboo types.The best of isothermal adsorption.Of ion H+ andong charcoal was 3,87 x 10-6 mol/liter/g at the temperature pyrolization 600 degree C with value of K1 = 0,03351,petung charcoal was 1,25 x10-5 mol/liter/g at the temperature pyrolization 400 degree C with value of K1 =0,02888 and the korea charcoal was 5,34 x 10-6mol/liter/g at the temperature pyrolization 700 degree C with value of K1=0,02849 respectively.The best of chloroform adsorption for the andong caharcoal 262.0%,the petung charcoal 180.5% and the korea charcoal 125,7% at temperature pyrolization 700 degree C.The best of the electrical conductivity for the korea charcoal and the andong charcoal was ranged beetwen 0,37-2.54 MQ.